Combining in vitro and in vivo screening to identify efficient Pseudomonas biocontrol strains against the phytopathogenic bacterium Ralstonia solanacearum. Issue 2 (14th April 2022) - Clough, Sophie E.; Jousset, Alexandre; Elphinstone, John G.; Friman, Ville‐Petri
Abstract: Although plant pathogens are traditionally controlled using synthetic agrochemicals, the availability of commercial bactericides is still limited. One potential control strategy could be the use of plant growth‐promoting bacteria (PGPB) to suppress pathogens via resource competition or the production of antimicrobial compounds. This study aimed to conduct in vitro and in vivo screening of eight Pseudomonas strains against Ralstonia solanacearum (the causative agent of bacterial wilt) and to investigate underlying mechanisms of potential pathogen suppression. We found that inhibitory effects were Pseudomonas strain‐specific, with strain CHA0 showing the highest pathogen suppression. Genomic screening identified 2, 4‐diacetylphloroglucinol, pyoluteorin, and orfamides A and B secondary metabolite clusters in the genomes of the most inhibitory strains, which were investigated further. Although all these compounds suppressed R. solanacearum growth, only orfamide A was produced in the growth media based on mass spectrometry. Moreover, orfamide variants extracted from Pseudomonas cultures showed high pathogen suppression. Using the "Micro‐Tom" tomato cultivar, it was found that CHA0 could reduce bacterial wilt disease incidence with one of the two tested pathogen strains. Together, these findings suggest that a better understanding of Pseudomonas – Ralstonia interactions in the rhizosphere is required to successfully translate in vitro findings into agricultural applications. Abstract : This study aimed to conduct in vitro and in vivo screening of eight Pseudomonas strains against Ralstonia solanacearum (the causative agent of bacterial wilt) and to investigate underlying mechanisms of potential pathogen suppression. Genomic screening identified 2, 4‐diacetylphloroglucinol, pyoluteorin, and orfamides A and B secondary metabolite clusters in the genomes of the most inhibitory strains, which all suppressed R. solanacearum growth. Although Pseudomonas could reduce bacterial wilt disease incidence with tomato, the effect depended on the R. solanacearum strain, highlighting the need to better understand Pseudomonas – Ralstonia interactions in the rhizosphere.